The Role Of The Legal Aid Post Is In Providing Legal Assistance To Disadvantaged People In Order To Obtain Justice In The Courts Of The Holy Land - Hartoyo*, Rudi; Sulistyowati, Sulistyowati (Universitas Syiah Kuala, 2023)
Providing legal assistance is one of the manifestations of the mandate of Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The mention of equal rights before the law in the 1945 Constitution of the Republic of Indonesia brings certain consequences, both to their qualifications and which parties have primary obligation to fulfill them. This research method uses an empirical/ sociological or non-doctrinal juridical approach. The results of the study show that the role of the Legal Aid Post in serving people who cannot afford to get justice at the Kudus District Court, only provides information, consultation or legal advice that does not reach the stage of accompanying or representing in the courtroom, preparing the documents needed for applicants for Legal Aid Post services who can't afford it as well as providing information on a list of legal aid organizations that can provide legal aid free of charge (prodeo). The Kudus District Court Legal Aid Post provides legal assistance to people who can't afford it, it is limited to providing information, consultation or legal advice that doesn't reach the stage of accompanying or representing in the courtroom, making the documents needed for applicants for the Legal Aid Post service who can't afford it. as well as providing information on a list of legal aid organizations that can provide legal aid free of charge (prodeo) which is an implementation of the state's responsibility in providing legal aid to the community.